Two salivary proteins Sm10 and SmC002 from grain aphid Sitobion miscanthi modulate wheat defense and enhance aphid performance - Fu, Yu; Liu, Xiaobei; Wang, Qian; Liu, Huan; Cheng, Yumeng; Li, Hongmei; Zhang, Yong; Chen, Julian (Frontiers in Plant Science, 2023)
Grain aphid Sitobion miscanthi is a serious pest of wheat, causing seriously economic damage through sucking phloem sap and transmitting plant viruses. Here, two putative salivary effector homologs from S.miscanthi (Sm10, SmC002) were selected based on sequence similarity to the other characterized aphid candidate effectors, then were delivered into wheat cells separately, via the type III secretion system (T3SS) of Pseudomonas fluorescens, to identify their functions in regulating plant defenses and host fitness. The results showed that delivering either Sm10 or SmC002 into wheat plant significantly suppressed the pattern-triggered immunity (PTI)-associated callose deposition and the transcript levels of callose synthase genes. The expression levels of salicylic acid (SA)-associated defense genes were upregulated significantly in wheat leaves delivered with either Sm10 or SmC002, but significantly inhibited jasmonic acid (JA)-related defense genes. And, LC-MS/MS analysis showed that wheat SA levels were significantly increased after delivering the two effectors, respectively. The aphid bioassays were conducted on the expressed wheat with Sm10 or SmC002, the result showed significantly increased survival and fecundity of S. miscanthi. This study demonstrated that salivary effectors Sm10 and SmC002 of S. miscanthi enhanced host plant susceptibility and benefit S. miscanthi performance by regulating wheat defense signaling pathways.